Educação bilingue para surdos: práticas discursivas em tempos de exclusão - Bosco, Daniella Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Studying bilingual education for the deaf students in different contexts of escolarization implies in an approximation of a complex phenomenon of educational reality and fraught with tensions in which competing forces of different segments of society in an attempt to define the best institutional setting, that bilingual education can tale on within formal education systems. Considering this problem, this research focuses on analyzing the contributions of discursive practices in the constitution of bilingual subjects in two educational spaces: an inclusive school with bilingual proposition and a bilingual school for the deaf. Thus, the theoretical framework for this study comes from the contributions of cultural-historical psychology and Bakhtin’s dialogical principle and addition to the reference works in the field of deafness. To accomplish these objectives were made surveys of discursive practices involving different subjects present in the classroom, in two schools were conducted that adopted the bilingual education philosophy.As investigation procedures data was collected through observations and filming of discursive practices in the classroom. Data were collected from March 2012 to March 2013 and, after collection, the material obtained with filming underwent transcription as proposed in Quadros and Karnopp (2004) and Lodi (2006) studies. The selection of fragments referring to data collected through video recordings and observations of discursive practices occurred by movement back to the epistemological and theoretical assumptions which led to the development of this research.The search for the selection of fragments of enunciation deduced the detailed assessment of enunciation shared between teacher, interpreter, hearing and deaf students (inclusive education) and bilingual teacher and deaf students (bilingual school for the deaf), during the process of production of meanings in the classroom. The focus of this analysis focused...

Estudar a educação bilíngue para surdos em diferentes contextos de escolarização implica em uma aproximação de um fenômeno da realidade educacional complexo e repleto de tensões, no qual concorrem forças de diferentes segmentos da sociedade, na tentativa de se definir a melhor configuração institucional, que a educação bilíngue pode assumir dentro dos sistemas formais de ensino. Considerando essa problemática, a presente pesquisa tem como foco analisar as contribuições das práticas discursivas na constituição de sujeitos bilíngues, em dois espaços educacionais: uma escola inclusiva com proposição bilíngue e uma escola bilíngue para surdos. O referencial teórico adotado constituiu-se a partir dos aportes da psicologia histórico-cultural e do princípio dialógico de Bakhtin, além das obras de referência na área da surdez. Para cumprir tais objetivos foram realizados levantamentos das práticas discursivas envolvendo diferentes sujeitos presentes em sala de aula, em duas escolas que adotavam a filosofia educacional bilíngue. Como procedimentos de investigação foram utilizados videogravações e observações das práticas discursivas realizadas em sala de aula. Os dados foram coletados no período de março de 2012 a março de 2013 e, após a coleta, o material obtido com as filmagens foi submetido à transcrição conforme proposto nos estudos Quadros e Karnopp (2004) e Lodi (2006). A seleção dos fragmentos referentes aos dados coletados por meio das videogravações e observações das práticas discursivas ocorreu pelo movimento de retorno aos pressupostos epistemológicos e teóricos do qual originou o desenvolvimento desta pesquisa. A busca pela seleção dos fragmentos das enunciações depreendeu a apreciação pormenorizada das enunciações compartilhadas entre professor, intérprete, alunos ouvintes e surda (escola inclusiva) e professor bilíngue e alunos surdos (escola bilíngue para surdos)...
Keywords: Educação bilingue; Educação inclusiva; Surdez; Língua brasileira de sinais; Inclusive education